Issues of Regulation of the Practice of Lending to Individuals by Commercial Banks of the Republic of Uzbekistan - Кulliev Istam Yangimurodovich (European Journal of Life Safety and Stability (2660-9630), 2023)
Direct or indirect regulation of lending practices in the banking and financial system serves to prevent and minimize negative situations that may occur. In particular, coordination of lending practices of commercial banks to individuals, regulation of borrowers and co-borrowers through debt burden is widely used in international practice. In this regard, regulation of lending practices of individuals in commercial banks by the Central Bank and its improvement is considered a key factor in sustainable development of the banking system. In this article, the theoretical aspects of lending to individuals are researched and relevant recommendations are developed